Hubungan Stres Dengan Status Gizi Pada Mahasiswa Gizi Angkatan 2023 Universitas Sultan Ageng Tirtayasa - Aisha Zahwa Shabira; Dea Asyifa Fitri; Lulu Sabrina Alamanda; Nafisa Zayyan Aulia (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Stress often occurs in students, there are several factors that influence the occurrence of stress, one of which is the difference between the desired situation and conditions and the conditions that occur. The purpose of this research is to find out how stress is related to nutritional status in students of the Sultan Ageng Tirtayasa University nutrition study program. This research is an analytical research using a sample of 20 people. Data were collected using anthropometric measurements through questionnaires including height, weight, body mass index as well as measuring stress levels obtained using the DASS 42 questionnaire score. The results of this research showed that 17 respondents (75%) of students experienced moderate stress. and the majority of respondents (40%) had thin and normal nutritional status. Conclusions obtained from research have shown that nutritional status and stress levels have no correlation.